A geotouristic valuation of the Marsyangdi Valley in the Annapurna Himal region and its potential for the development of geotourist attractions // Ocena geoturystyczna doliny Marsyangdi regionu Annapurny Himal i jej potencjał w tworzeniu atrakcji geotur. - Łach, Janusz (Geotourism/Geoturystyka, 2017)
The Marsyangdi Valley in the Annapurna Himal region is one of the most popular tourist-trekking attractions in Nepal. The performed evaluation of geotourist (geomorphological and hydrographic) objects and phenomena demonstrated a wide range of forms and, correspondingly, a huge potential for the develop- ment of geotourist attractions. The structure of The Marsyangdi Valley, which is a representative of a valley region of the High Himalaya, situated on metamorphic rocks, shows the co-existence of three major geomorphic processes: glacial, fuvial and slope, which determine specifc landscape forms. Since the late 20th cen- tury, the landscape has been heavily affected by anthropogenic factors (grazing, land cultivation, settlement), reaching as far as 3500 meters above sea level, as well as by the dynamic growth and development of tourism. Expanding tourist infrastructure contributes to, inter alia, the degradation of the narrow valley bottom (tourist accommodation) and to increased mass movement on tourist trails. Despite its negative effects, tourism also exerts a positive infuence on the preservation of the cultural heritage (sacred sites), which largely dominate the landscape and are a signifcant tourist attraction. The research was instrumental in de- fning the Marsyangdi Valley, characteristic of a geomorphologi- cal trail, as an excellent and qualifed attraction in geotourist-ex- ploratory tourism. //Dolina Marsyangdi należąca do regionu Annapurny Himal jest jedną z najpopularniejszych atrakcji turystycznych – trekkin- gowych Nepalu. Przeprowadzona pod kątem obiektów i zjawisk geoturystycznych (geomorfologicznych i hydrografcznych) ocena ukazała jej dużą różnorodność form, a tym samym duży poten- cjał atrakcji geoturystycznych. W strukturze doliny Marsyangdi, będącej przykładem dolin obszaru Himalajów Wysokich, wy- różniono współistnienie trzech głównych procesów geomorfolo- gicznych: glacjalnych, fuwialnych i stokowych, warunkujących specyfczne formy o wysokich walorach krajobrazowych, które od końca XX wieku podlegają szybkiej destrukcji w wyniku an- tropopresji. Czynniki antropogeniczne tj. hodowla, uprawa, czy osadnictwo sięgające nawet do 3500 m n.p.m., a obecnie jesz- cze turystyka, przyczyniają się do wzrostu aktywności procesów geomorfologicznych m.in. ruchów masowych, w tym na szlakach turystycznych. Jednakże oprócz negatywnego wpływu turystyki na uwagę zasługuje jej pozytywne oddziaływanie w szczególno- ści w kwestii ochrony dziedzictwa kulturowego, czego przykładem są odnawiane obiekty sakralne stanowiące niezwykłą dominantę krajobrazu oraz istotną atrakcję turystyczną. Badania pozwoliły zdefniować obszar Doliny Marsyangdi jako odpowiedni do upra- wiania turystyki kwalifkowanej, poznawczej – geoturystyki.